Intestinal and multivisceral transplantation. Issue 7 (July 2020) - Russell, Neil
Abstract: Intestinal and multivisceral transplantation can be a lifesaving treatment for patients with complications from the treatment of intestinal failure. However, the indications for this highly specialized treatment are broadening and include other such indications as patients with acute abdominal vascular catastrophes as well as patients with previously unresectable benign intra-abdominal tumours. Since the first successful multivisceral transplant in the late 1980s, the field has expanded and more than 4000 transplants have taken place worldwide and outcomes continue to improve. However, complications are still commonplace and multivisceral and intestinal transplant recipients are more likely to suffer from the complications of transplantation than any other solid organ transplant group. The most important complications are rejection and sepsis, with sepsis remaining the leading cause of death in this patient group. That said the outcomes for intestine alone transplants have improved to such a degree that they are close to that of intestinal failure patients on long-term parenteral nutrition and therefore we may be entering an era where intestinal transplantation will be offered as an alternative to parenteral nutrition for patients with intestinal failure.